Listening self-efficacy beliefs, L2 listening proficiency, and listening strategy training - Hamdi Khosroshahi, Hamideh; Merc, Ali (ELT Forum: Journal of English Language Teaching, 2020)
Self-efficacy plays an important role in language learners' performances in language learning. Studies report that explicit teaching of strategies, self-efficacy, and better learner performance are interdependent concepts. This entails the fact that language teachers should focus on the first two in order to increase the learners' performance. The aim of this study is to find out how teaching cognitive and metacognitive strategies affect EFL learners' performances and self-efficacy beliefs in listening comprehension tasks. Ninety students participated in this study, thirty of whom were part of the control group. Their listening self-efficacy and listening proficiency were measured before and after a four-week training. During the intervention sessions, instructors taught cognitive and metacognitive strategies in an explicit way, which included teacher modeling and teacher feedback. The results revealed that learners' listening proficiency scores increased while their self-efficacy scores did not change significantly after the training. These findings led to the conclusion that low self-efficacy does not necessarily lead to low listening proficiency. Another finding was that teaching only cognitive and metacognitive strategies do not help learners with their self-efficacy in a short time period. Implications and suggestions for L2 listening are provided considering the results of the study.